CD4(+) T cell subsets during virus infection. Protective capacity depends on effector cytokine secretion and on migratory capability. - Maloy, K; Burkhart, C; Junt, T; Odermatt, B; Oxenius, A; Piali, L; Zinkernagel, R; Hengartner, H (2000)
To analyze the antiviral protective capacities of CD4(+) T helper (Th) cell subsets, we used transgenic T cells expressing an I-A(b)-restricted T cell receptor specific for an epitope of vesicular stomatitis virus glycoprotein (VSV-G). After polarization into Th1 or Th2 effectors and adoptive transfer into T cell-deficient recipients, protective capacities were assessed after infection with different types of viruses expressing the VSV-G. Both Th1 and Th2 CD4(+) T cells could transfer protection against systemic VSV infection, by stimulating the production of neutralizing immunoglobulin G antibodies. However, only Th1 CD4(+) T cells were able to mediate protection against infection with recombinant vaccinia virus expressing the VSV-G (Vacc-IND-G). Similarly, only Th1 CD4(+) T cells were able to rapidly eradicate Vacc-IND-G from peripheral organs, to mediate delayed-type hypersensitivity responses against VSV-G and to protect against lethal intranasal infection with VSV. Protective capacity correlated with the ability of Th1 CD4(+) T cells to rapidly migrate to peripheral inflammatory sites in vivo and to respond to inflammatory chemokines that were induced after virus infection of peripheral tissues. Therefore, the antiviral protective capacity of a given CD4(+) T cell is governed by the effector cytokines it produces and by its migratory capability.